Hybrid Inventory Management for Manufacturing-Remanufacturing Process (a Literature Review) - Olivia M. de Fretes (Industrial Engineering Study Program, Pattimura University, 2011)
Inventory management deals with determining the exact time and quantity of order to support the production plan. Excessive inventories incur extra cost while insufficient inventories can ruin the production schedule, hurting both the strategic value elements of delivery dependability and speed. This indicates that inventory is a crucial element of the production process. This literature review is addressed to the management of inventory in manufacturing process as well as the one in remanufacturing separately, and at the end, the inventory management in system where manufacturing and remanufacturing process occur simultaneously. Recommendations for future work are proposed at the end of this review.